A brief Analysis and study of Rewards and promotion policy - Tayyab Ansari (Journal of Advanced Research in Operational and Marketing Management, 2020)
Strategic reward management is the process of looking ahead at what an organization needs to do about its reward policies and practices in the middle or relatively distant future. It is concerned with the broader business issues the organisation is facing and the general directions in which reward management must go to provide help in dealing with these issues to achieve longer-term business goals. In this paper rewards and promotion policy is discussed. The paper includes discusses policies using various study, structure, and models. How to cite this article: Ansari T. A Brief Analysis and Study of Rewards and Promotion Policy. J Adv Res Oper Markt Mgmt 2020; 3(2): 1-12.